Enhancing Speaking Performance of Sophomore Students in an Indonesian Senior Highschool Context Using Offline Youtube Videos - Muh Erwin; Badaruddin Badaruddin; Rafi’ah Nur (Tamaddun Life, 2021)
Speaking is considered to be one difficulties faced by the students. There are some problems as causes of the students’ difficulties in speaking, such as they are afraid of making mistake, seldom to communicate and cannot express their ideas. To solve the problems, the authors suggests applying Offline YouTube Videos in learning process. Based on the previous explanation, the authors formulates the objective of the study is to find out whether or not the speaking ability of the eleventh-year students of SMA Negeri 2 Pinrang can improve using Offline YouTube Videos. In this study, the authors applied quasi-experimental method, with two group namely experimental class and control class. The samples was chosen using cluster random sampling technique. The total numbers of sample were consisted of 32 students from two classes taken from the population of the eleventh year students of SMA Negeri 2 Pinrang. The instrument used in this study was speaking test by record the students’ utterance. The data were analyzed by using t-test formula. The result of the data analyzed shows that the students’ speaking ability improved significantly. It can be proved that the mean score of students’ post-test in experimental class (59.68) was higher than the control class (49.06). Moreover, the probability value (0.012) was lower than the significance value (α)=(0.05). The analysis showed that the alternative hypothesis (H1) was accepted. It means that the eleventh year students’ speaking ability at SMA Negeri 2 Pinrang. for experimental class and control class was significant difference between the speaking ability of the students who were taught using Offline YouTube Videos and the speaking ability of the students who were thought by using Instagram Videos.